Not Catalan's Constant

Calculus Level 5

n = 0 ( 1 ) n ( 2 n + 1 ) 3 = π A B \large \displaystyle \sum_{n=0}^{\infty} \dfrac{(-1)^n}{(2n+1)^3} = \dfrac{\pi^A}{B}

If the equation holds true for positive integers A A and B B , find A + B A+B .


The answer is 35.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Aditya Kumar
Aug 4, 2016

n = 0 ( 1 ) n ( 2 n + 1 ) 3 = 1 1 3 3 + 1 5 3 1 7 3 + = ( 1 + 1 5 3 + 1 9 3 + 1 1 3 3 + ) ( 1 3 3 + 1 7 3 + 1 1 1 3 + ) = n = 0 1 ( 4 n + 1 ) 3 n = 1 1 ( 4 n 1 ) 3 = n = 0 1 ( 4 n + 1 ) 3 n = 0 1 ( 4 n 1 ) 3 1 = 1 4 3 [ n = 0 1 ( n + 1 / 4 ) 3 n = 0 1 ( n 1 / 4 ) 3 ] 1 = 1 4 3 [ ψ 2 ( 1 / 4 ) 2 + ψ 2 ( 1 / 4 ) 2 ] 1 = π 3 32 \begin{aligned} \sum_{n=0}^\infty \dfrac{(-1)^n}{(2n+1)^3} &=& 1 - \dfrac1{3^3} + \dfrac1{5^3} - \dfrac1{7^3} + \cdots \\ &=& \left( 1 + \dfrac1{5^3} + \dfrac1{9^3} + \dfrac1{13^3} + \cdots \right) - \left( \dfrac1{3^3} + \dfrac1{7^3} + \dfrac1{11^3} + \cdots \right) \\ &=& \sum_{n=0}^\infty \dfrac1{(4n+1)^3} - \sum_{n=1}^\infty \dfrac1{(4n-1)^3} \\ &=& \sum_{n=0}^\infty \dfrac1{(4n+1)^3} - \sum_{n=0}^\infty \dfrac1{(4n-1)^3} - 1 \\ &=& \dfrac 1{4^3} \left [ \sum_{n=0}^\infty \dfrac1{(n+1/4)^3} - \sum_{n=0}^\infty \dfrac1{(n-1/4)^3} \right ] - 1 \\ &=& \dfrac1{4^3} \left [-\dfrac{\psi_2(1/4)}{2} + \dfrac{\psi_2(-1/4)}{2} \right ] - 1\\ &=&\dfrac{\pi^3}{32} \end{aligned}

For the last step reasoning is: use recursive formula for polygamma function and then use reflection formula for polygamma function and simplify.

Mark Hennings
Jul 30, 2016

Let D N D_N be the square contour with vertices at ϵ N + i η N \epsilon N + i\eta N for ϵ , η = 1 , 1 \epsilon,\eta = -1,1 . The function f ( z ) = π sec π z f(z) = \pi \sec \pi z is meromorphic, even and antiperiodic with (anti)period 1 1 . Moreover f ( z ) π |f(z)| \le \pi for all z D N z \in D_N for all N N N \in \mathbb{N} . Thus 1 2 π i D N f ( z ) z 3 d z = R e s z = 0 f ( z ) z 3 + n = 0 N 1 ( R e s z = n + 1 2 + R e s z = n 1 2 ) f ( z ) z 3 \frac{1}{2\pi i}\int_{D_N} \frac{f(z)}{z^3}\,dz \; = \; \mathrm{Res}_{z=0} \frac{f(z)}{z^3} + \sum_{n=0}^{N-1}\left(\mathrm{Res}_{z=n+\frac12} + \mathrm{Res}_{z = -n-\tfrac12}\right) \frac{f(z)}{z^3} for any N N N \in \mathbb{N} . Letting N N \to \infty , and using the evenness of f ( z ) f(z) , we deduce that 0 = R e s z = 0 f ( z ) z 3 + 2 n = 0 R e s z = n + 1 2 f ( z ) z 3 0 \; = \; \mathrm{Res}_{z=0} \frac{f(z)}{z^3} + 2\sum_{n=0}^\infty\mathrm{Res}_{z=n+\frac12}\frac{f(z)}{z^3} But this tells us that 0 = 1 2 π 3 2 n = 0 ( 1 ) n ( n + 1 2 ) 3 0 \; = \; \tfrac12\pi^3 - 2\sum_{n=0}^\infty \frac{(-1)^n}{(n+\frac12)^3} and hence that n = 0 ( 1 ) n ( 2 n + 1 ) 3 = 1 32 π 3 \sum_{n=0}^\infty \frac{(-1)^n}{(2n+1)^3} \; = \; \tfrac{1}{32}\pi^3 making the answer 3 + 32 = 35 3 +32 = \boxed{35} .

You can show the series is equal to the integral much faster, by noting that 1 2 0 x 2 e x 1 + e 2 x d x = 1 2 n = 0 ( 1 ) n 0 x 2 e ( 2 n + 1 ) x d x = n = 0 ( 1 ) n ( 2 n + 1 ) 3 \tfrac12\int_0^\infty \frac{x^2 e^{-x}}{1 + e^{-2x}}\,dx \; = \;\tfrac12\sum_{n=0}^\infty (-1)^n \int_0^\infty x^2 e^{-(2n+1)x}\,dx \; = \; \sum_{n=0}^\infty \frac{(-1)^n}{(2n+1)^3}

The substitution y = e 2 x y = e^{-2x} converts the integral to the second derivative of a Beta function.

Mark Hennings - 4 years, 10 months ago

I didn't write the solution of the integral because it is a bit long.

Vittorio D'Esposito - 4 years, 10 months ago

Log in to reply

I would suggest to put that in, since readers would be interested to see such a colorful derivation.

Aditya Narayan Sharma - 4 years, 10 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...